Relationship between Angiogenic Squamous Dysplasia and Bronchogenic Carcinoma in Patients Undergoing White Light Bronchoscopy. Issue 3 (2012) - Karimi, Shirin; Mohammadi, Forouzan; Khodadad, Kian; Sadr, Makan; Seyfollahi, Leila; Masjedi, Mohammad Reza
Abstract : OBJECTIVE: To better understand the characteristic morphology of angiogenic squamous dysplasia (ASD) and its association with different types of common bronchogenic carcinomas using routine white light bronchoscopy. METHODS: Using a case-control design, 186 formalin-fixed paraffin-embedded blocks of bronchial tissue (136 cases, 50 controls) obtained from patients who underwent routine nonfluorescence bronchoscopy between 2004 and 2005 were studied. RESULTS: ASD occurred at a higher frequency in patients with neoplastic lesions compared with those without neoplastic lesions (28 of 136 versus one of 50). ASD was also more prevalent in patients with squamous cell carcinoma compared with other neoplasms. Seventy six per cent of the ASD patients (22 of 29) smoked cigarettes. The morphology of ASD on hematoxylin and eosin- and CD31-stained sections was characterized by prominent microvasculature and capillary projections closely juxtaposed to variable degrees of dysplasia in all of the bronchogenic carcinoma specimens, and to metaplasia in one case in the control group. CONCLUSION: ASD is a unique morphological entity that should be considered by pathologists even on bronchoscopic biopsies from patients who undergo white light bronchoscopy. The presence of ASD may represent a risk biomarker of bronchogenic carcinoma in screening programs and in chemoprevention of lung cancer.